SAR Prediction and SAR Management for Parallel Transmit MRI - Homann, Hanno (Karlsruhe transactions on biomedical engineering / Ed.: Karlsruhe Institute of Technology / Institute of Biomedical Engineering, 2012)
Parallel transmission enables control of the RF field in high-field Magnetic Resonance Imaging (MRI). However, the approach has also caused concerns about the specific absorption rate (SAR) in the patient body. The present work provides new concepts for SAR prediction. A novel approach for generating human body models is proposed, based on a water-fat separated MRI pre-scan. Furthermore, this work explores various approaches for SAR reduction.